TFDP3 as E2F Unique Partner, Has Crucial Roles in Cancer Cells and Testis - Huang, Jiahao; Wang, Yini; Liu, Jinlong; Chu, Ming; Wang, Yuedan (Frontiers in Oncology, 2021)
Transcription factor Dp family member 3 (TFDP3) is a cancer-testis antigen, mainly expressed in normal testis and multiple cancers. TFDP3 gene (Gene ID: 51270) is located on the chromosome X and shares a high degree of sequence homology with TFDP1 and TFDP2, which can form heterodimers with E2F subunits and enhance DNA binding activity of E2Fs. In contrast to TFDP1 and TFDP2, TFDP3 downregulates E2F-mediated transcriptional activation. During DNA damage response in cancer cells, TFDP3 is induced and can inhibit E2F1-mediated apoptosis. Moreover, TFDP3 is involved in cell autophagy and epithelial-mesenchymal transition. Regarding cancer therapy opportunity, the transduction of dendritic cells with recombinant adenovirus encoding TFDP3 can activate autologous cytotoxic T lymphocytes to target hepatoma cells. Here, we review the characterization of TFDP3, with an emphasis on the biological function and molecular mechanism. A better understanding of TFDP3 will provide new insights into the pathological mechanisms and therapeutic strategies for cancers.